Multidrug Resistance and Virulence Profiles ofSalmonellaIsolated from Swine Lymph Nodes - Azevedo, Everton Cruz de; Martins, Bruna Torres Furtado; Tiba Casas, Monique Ribeiro; Possebon, Fabio Sossai [UNESP]; Araujo Junior, Joao Pessoa [UNESP]; Nero, Luis Augusto; Yamatogi, Ricardo Seiti (Mary Ann Liebert, Inc, 2020)
Salmonellaspp. is a foodborne pathogen present in the pork production chain, leading to potential contamination of end products and causing salmonellosis cases and outbreaks worldwide. The emergence of multidrug-resistant (MDR)Salmonellaspp., especially isolates obtained from animal origin food, is a global concern. This study aimed to isolateSalmonellafrom swine mesenteric lymph nodes (MLN) and to characterize the virulence and antibiotic resistance profiles. MLN samples were obtained from a swine slaughterhouse and subjected toSalmonellaspp. isolation. Ten MLN samples were positive and 29 isolates were identified based on PCR (invAandompC) and serotyping: Derby, Cerro, and Give. Pulsed-field gel electrophoresis allowed to group the isolates based on their serotypes, resulting in three major clusters. All isolates presented the virulence-related genespefA,sipA,sopB,spaN, andpagC. Relatively high numbers ofSalmonellaspp. were resistant to neomycin, polymyxin B, ciprofloxacin, tetracycline, and nalidixic acid. Furthermore, 25 isolates presented simultaneous resistance to three or more antibiotic classes, being characterized as MDR. The obtained results confirmed the relevance of swine as reservoirs ofSalmonellaspp. in the pork production chain and demonstrated the MDR profiles of isolates. Proper control and surveillance are required to avoid the contamination of end products.
Keywords: Salmonellaserovars; antibiotic resistance; virulence genes; lymph nodes